Conversational repair, gender, and interactional competence in an Indonesian EFL classroom: Insights and implications - Utami, Almira (Universitas Negeri Semarang, 2025)
This article provides a qualitative examination of conversational repair in an Indonesian EFL (English as a Foreign Language) classroom, focusing on how gender differences in initiating repair strategies are indicative of the EFL learners’ interactional competence (IC). Based on data from a case study approach involving ten adult students, five male and five female students, in an English course class, the article contributes to an in-depth insight into how male and female students handle communication problems. The results show that there are patterns: female students tend to utilize “weaker” or less specific repair initiators, suggesting a pragmatic orientation to politeness, as well as a collaborative approach to the identification of problems. In contrast, male students mainly employ